ROLE OF ANTIOXIDANT AND INFLAMMATORY MARKERS WITH METABOLIC SYNDROME AND RISK OF CVD IN THYROID PATIENTS - RAVI SHANKAR; AJAY KUMAR; NEHA SHARMA; RAJU RAM; APARAJITA KUSHWAHA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Metabolic syndrome is the most widely used term for the aggregation of metabolic abnormalities, which leads to an increase in the risk of developing cardiovascular pathology. Protective nutritional antioxidants may benefit defensive antioxidative systems in resolving pro-oxidative dominance and redox imbalance, preventing, or delaying chronic thyroid diseases. Methods: This cross-sectional, observational study was conducted among metabolic syndrome patients in the general population and near and dear patients (350) at the Pacific Institute of Medical Sciences, Udaipur. For the determination of interleukin-6 (IL-6) was done by enzyme-linked immunosorbent assay. Thyroid hormones are determined by chemiluminescence and antioxidant Vitamin C and malondialdehyde (MDA) chromatography and high-performance liquid chromatography, respectively. Results: This study shows a low level of antioxidant Vitamin C and MDA and a high level of inflammatory marker IL-6 in these patients. In this study, the age distribution of patients showed that males in the 35–51 years of age group were most affected, whereas females in the 18–34 years of age group were more prevalent. Conclusion: The present study leads to awareness of antioxidant levels and inflammation in thyroid patients along with other biochemical parameters involved in the development of metabolic syndrome in the Indian population.